PENGARUH PENDAPATAN ASLI DAERAH, BELANJA MODAL TERHADAP PERTUMBUHAN EKONOMI DAN DANA PERIMBANGAN SEBAGAI PEMODERASI DI KABUPATEN/KOTA SUMATERA UTARA - Putra, Ardhansyah (JKBM (JURNAL KONSEP BISNIS DAN MANAJEMEN), 2016)
The objective of the research was to examine and to prove empirically the influence of regionally generated revenue and capital expenditures on economic growth in districts/towns of North Sumatera and to examine balance fund as moderating variable, The population was 33 districts/towns (25 districts and 7 towns) in North Sumatera. The samples (25 districts and 7 towns) had met the criteria during within years of observation so that there were 150 observations. The data consisted of PDRTB (Gross Regional Domestic Product) on constant price in order to find out the economic growth in districts/towns of North Sumatera, realization of PAD (regionally generated revenue), capital expenditure, and balance fund. The data were obtained from the Central Bureau of Statistics of North Sumatera and analyzed by using multiple linear regression analysis and residual analysis. The result of the research, using t-test, showed that partially PAD had positive and significant influence on economic growth, and capital expenditure had positive and significant influence of economic growth. The result of the research, using F-test, showed that simultaneously PAD and capital expenditure had influence on economic growth, while based on residual test it showed that balance fund did not moderate the correlation of PAD and capital expen diture and economic growth..Keywords: Regionally Generated Revenue, Capital Expenditures, Balance Fund, Economic Growth